Alice's Restaurant [videorecording (DVD)] - Penn, Arthur, 1922-2010; Guthrie, Arlo; Quinn, Patricia, 1937-; Broderick, James (MGM Home Entertainment Inc., 2002)
"In the late '60s, a changing social and political climate inspired a new generation to create a lifestyle outside the mainstream. Twenty-two year-old Arlo's journey to find a place for himself and his music includes a visit to his dying father in the hospital, gigs in New York and romps with his friends Alice and Ray, who run a small restaurant in Stockbridge, Massachusetts. And when an incident at Alice's Restaurant plays a pivotal role in Arlo's avoidance of the draft, it send him down a road that he will consider a small price to pay to keep his freedom and his beliefs"--Container.